ETIKA BISNIS DI ERA DIGITALISASI DAN PENEGAKAN HUKUMNYA DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN - Situmeang, Sahat Maruli Tua; Limbong, Beatrik Juliany; Utomo, Subagyo Sri; Wuntu, Happy Ferovina; Diah Pudjiastuti; Sutarjo (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2025)
Basically, in the business world, the main goal is to achieve profits. However, it is important to remember that businesses that violate ethical principles require strong law enforcement to protect legal values. This is necessary because there are still companies that try to take advantage of legal loopholes to gain profits. Therefore, this research aims to investigate and understand how the law regulates ethical violations in the business context in the digital era, including regulations and how they are implemented. The research method used is legal research based on applicable norms. The research results show that the law has regulated protection against ethical violations in statutory regulations. However, in practice, providing sanctions for violations of business ethics is still ineffective, due to various factors, including the lack of legal provisions that address corporate social and environmental responsibilities.